Pastoral training in the Christian church ; pt 2 a doctoral course work research project - McNaught, James Stewart, 1919-1987
Includes bibliographical references.
A project submitted in partial fulfillment of the requirements for the degree of Doctor of Education, in Education Programme, California Coast University, July 1982. Brethren writer.
Keywords: Pastoral training -- history